Violation of Standard Operating Procedures (Smile, Greet, Say Hello) in the Company's Regulations on Employment - Saputri, Ariyanti Sofiya; Pello, Helsina Fransiska; Kaesmetan, Rini Marselin (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Violation of the Standard Operating Procedure (SOP) of Smile, Greet, Say Hello is a form of violation of minor work discipline in Company Regulations or Collective Labor Agreements. Sanctions for this violation are generally in the form of verbal and written reprimands, to a Warning Letter in stages in accordance with the provisions of labor law. Purposes of the Research: This study aims to juridically analyze violations of the Smile, Greeting, and Salutation Standard Operating Procedure (Smile, Greet, Say Hello SOP) in company regulations based on Law Number 13 of 2003 concerning Manpower. The study focuses on the legal position of the Smile, Greet, Say Hello SOP in employment relationships, employees’ obligations to comply with company regulations, the classification of Smile, Greet, Say Hello SOP violations, as well as the mechanisms for dispute resolution and sanction implementation. Methods of the Research: This research employs a normative legal research method using statutory, conceptual, and analytical approaches. The legal materials consist of primary, secondary, and tertiary legal sources collected through library research and analyzed descriptively and qualitatively. Findings of the Research: The results indicate that the Smile, Greet, Say Hello SOP has the status of a valid and binding internal company norm when stipulated in company regulations or collective labor agreements in accordance with labor law provisions. Violations of the Smile, Greet, Say Hello SOP are generally classified as minor disciplinary violations, the settlement of which should prioritize guidance, verbal warnings, and written warning letters applied progressively. The imposition of sanctions must be proportional, objective, and consistent with the principles of worker protection and legal certainty. The mechanism for resolving SOP violations is carried out through internal company procedures, bipartite negotiations, mediation, and the Industrial Relations Court in the event of disputes. Therefore, the implementation of the Smile, Greet, Say Hello SOP not only functions to establish a professional work culture and excellent service but must also ensure a balance of rights and obligations between employees and employers within industrial relations